Misi dan kebangkitan Rohani: Implikasi Misi Allah Bagi Gereja - Yosua Feliciano Camerling; Hengki Wijaya (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2019)
The purpose of this writing is to explain the close relationship between mission and spiritual awakening. The method used is qualitative description with library studies seen from the history of spiritual awakening that has happened and Christian mission's understanding of spiritual awakening. In conclusion, spiritual awakening can revive the passion for mission, and mission is one of the concrete steps manifested by missionaries in the event of a spiritual resurrection. For this reason, the signs that arise when spiritual awakening occurs are the heart of the mission involved. The relationship between mission and spiritual awakening is a spiritual awakening to evoke the spirit of mission. This is marked by so many missionaries who are involved in missionary service. Tujuan penulisan ini untuk menjelaskan hubungan yang erat antara misi dan kebangkitan rohani. Metode yang digunakan adalah kualitatif deskripsi dengan studi kepustakaan dilihat dari sejarah kebangkitan rohani yang pernah terjadi dan pemahaman misi Kristen terhadap kebangkitan rohani. Sebagai kesimpulannya adalah kebangkitan rohani dapat menghidupkan kembali gairah untuk bermisi, dan misi adalah salah satu langkah yang kongkret yang diwujudnyatakan oleh para misionaris ketikaterjadinya kebangkitan rohani. Untuk itu, tanda-tanda yang muncul saat kebangkitan rohani terjadi adalah hati misi ikut di dalamnya. Hubungan antara misi dan kebangkitan rohani ialah kebangkitan rohani membangkitkan semangat bermisi. Hal ini ditandai dengan begitu banyaknya misionaris yang terjun dalam pelayanan misi.